Enhancing community awareness of antimicrobial use and resistance through community conversations in rural Ethiopia - Lemma, Mamusha; Alemu, Biruk; Amenu, Kebede; Wieland, Barbara; Knight-Jones, Theodore J.D. (BioMed Central, 2025)
Background: Enhanced availability of veterinary drugs in Ethiopia has led to a growing use of these drugs in food-producing animals. However, the use of drugs in livestock is not commonly supervised by trained veterinarians. In addition, smallholder livestock producers often lack sufficient education and information about antimicrobial use to achieve the intended impact.